(untitled) (Pesquisa Odontológica Brasileira, 2000)
Since fluoride’s properties are widely known in the field of Preventive Dentistry, fluoride-releasing materials have been extensively investigated. Among the occlusal sealants, there is great expectation regarding the results that can be achieved with light-curing glass-ionomer cements due to their excellent properties. The aim of this study was to assess the use of one of these cements, Vitremer (3M) as an occlusal sealant. The material was applied using two different techniques; either associated or not with an adhesive system. After 6 and 12 months of observation, an evaluation was performed in 159 teeth to verify its retention as well as the presence of caries lesions. The technique that included the adhesive system showed better retention than the conventional one. Total retention was 84.9% for the experimental technique and 37.2% for the conventional technique after 12 months. There was no difference between bicuspids and molars regarding retention. Caries lesion was observed in a single tooth, for which a total loss of material was observed after one year.